Dual-Mobility Cups in Primary Total Hip Arthroplasty - Bellova, Petri; Goronzy, Jens; Riedel, Roman; Grothe, Tim; Hartmann, Albrecht; Günther, Klaus-Peter (The Journal of Hip Surgery, 2024)
Dual-mobility cups (DMCs) were introduced in France more than 40 years ago and are increasingly used not only in hip revision but also primary hip arthroplasty. Due to a simulated large-head articulation and increased jumping distance, DMCs can contribute to a high range of motion in the hip joint and reduce the risk of instability. Numerous studies have reported low dislocation rates and high survival rates in the mid-term follow-up. Nevertheless, long-term data, especially on primary hip replacement, remain limited, and the effect of recent designs and material innovations is still unclear. Therefore, primary DMCs are mainly proposed in patients at high risk for dislocation (i.e. pelvitrochanteric insufficiency, compromised spinopelvic mobility, neuromuscular disorders, obesity and femoral neck fractures). Based on a review of recently published studies referring to these indications, the current study discusses the advantages and disadvantages of DMCs.
Keywords: dual mobility; tripolar cups; hip arthroplasty; dislocation; instability